Keabsahan Perjanjian Pengikatan Jual Beli Yang Digantungkan Pada Kewajiban Pembayaran Utang - Denise Elysia (FAIRNESS AND JUSTICE, 2019)
The sale and purchase binding agreement is a legal breakthrough that was born out of the needs of the community. Used by the parties as a preliminary agreement because it has not been able to fulfill the conditions to carry out the sale and purchase before the officials of the land deed. However, in practice, binding of sale and purchase agreement is made not because of the sale and purchase transaction but as debt guarantee which the debtor plays as the seller and the creditor as the buyer. So the problem is how the legitimacy of binding agreement of sale and purchase as well as the sale power suspended as debt guarantee? then what is the basis of legal considerations for judges in deciding cases binding sale and purchase agreement that hung as debt guarantee ?. This research is a normative juridical research by using approach of legislation, concept and case. From the result of the research, it is concluded that the deed made by the parties before the notary is valid as an authentic deed which has been in accordance with the legislation, and the sale power is a unity in the sale and purchase agreement, where the seller authorizes the buyer to do duty rather than an authorizer. The sale power made by the parties is also an authentic deed and not an absolute authority prohibited by the Instruction of the Minister of Home Affairs Number 14/ 1982 because it does not contain an element of transfer of rights. Based on several considerations of the judge, it can be deduced that as long as the deed of sale and purchase agreement of sale and sale has been made and executed legally as authentic deed which has perfect evidentiary power, then the deed can not be canceled.